1966
DOI: 10.2307/1910101
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Cores in a Monetary Economy with Nonconvex Preferences

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Tue, A model of a pure exchange economy is investigated without the usual assumption of convex preference sets for the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
142
0
3

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(145 citation statements)
references
References 15 publications
(17 reference statements)
0
142
0
3
Order By: Relevance
“…Unfortunately, the core in general may be empty, e.g., the ticket-pricing problem that we consider in Chapter 8. Because of this reason, Shapley and Shubik generalized the core concept to the strong ε-core and weak ε-core [56], which are non-empty with suitable parameter ε. Following this line of reasoning, Maschler, Peleg, and Shapley [45] introduced in 1979 the least core, which is the intersection of all nonempty strong ε-cores.…”
Section: The Core and The F -Least Corementioning
confidence: 99%
“…Unfortunately, the core in general may be empty, e.g., the ticket-pricing problem that we consider in Chapter 8. Because of this reason, Shapley and Shubik generalized the core concept to the strong ε-core and weak ε-core [56], which are non-empty with suitable parameter ε. Following this line of reasoning, Maschler, Peleg, and Shapley [45] introduced in 1979 the least core, which is the intersection of all nonempty strong ε-cores.…”
Section: The Core and The F -Least Corementioning
confidence: 99%
“…Approximate cores of economies with quasi-linear utility functions were introduced in Shapley and Shubik (1966), which showed that when the player set is replicated, then, for all sufficiently large replications, approximate cores are nonempty. 12 A contribution by Owen (1975) is also relevant.…”
Section: Relationships To Prior Literature On Cooperative Games With mentioning
confidence: 99%
“…It has also been recognized that in private goods economies with many agents, problems of nonconvexities disappear or become insignificant; some seminal contributions are Aumann (1964), Shapley and Shubik (1966), Aumann and Shapley (1974), and, for economies with production, Hurwicz and Uzawa (1977). More specifically, in a number of situations it has been shown that, in economies with many agents, cores are nonempty, price-taking equilibria exist, and equilibrium outcomes are close to core outcomes, where approximations, if any, become arbitrarily good as the economies become large.…”
Section: Introductionmentioning
confidence: 99%
“…Since Shapley and Shubik [19] showing nonemptiness of approximate cores of exchange economies with many players and quasi-linear utilities and Wooders [23], [24], showing nonemptiness of approximate cores of game with many players with and without side payments, there has been a number of further results. For parameterized collections of games, such results are demonstrated in [6], [7], [8] and [28].…”
Section: Laws Of Scarcity Parameterized Collections Of Games and Equmentioning
confidence: 99%